Reflections on Paris: Thoughts Towards a Critical Approach to Climate Law - Dehm, Julia (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2018)
This article critically evaluates the 2015 Paris Agreement, highlighting the almost dichotomous responses it received from the mainstream press as compared to the climate justice movement. This article foregrounds that divide in order to ask further questions of the Agreement and the international climate regime, including questions about what voices and perspectives are heard in scholarship on international climate law. The article suggests the need to engage with international climate law in ways that are attentive to the productive effects of international agreements, as well as the need to examine their distributional effects, to interrogate what new social relations they establish and stabilize as well as how power and authority might be reorganized or rearranged by practices authorized by international environmental law.